EFVD along porcelain insulator using the FEM - Ho, Kian Tsong; Izadi, Mahdi; Ab Kadir, Mohd Zainal Abidin (Universiti Putra Malaysia Press, 2017)
In this paper, cap and pin porcelain insulator was studied under an environment with different levels of humidity. The electric field strength and voltage distribution profile along the insulator string was simulated using a computational software package. In this study, ANSYS Maxwell based on the Finite Element Method (FEM) was used to simulate the short standard insulator string. The short standard insulator string was modelled as a five-unit cap and pin porcelain insulator that was stacked according to the IEC 60383 standard. Different humidity levels measured using relative humidity is applied to the insulator. From this simulation, the locations within the insulator under high electric field stress are identified when different humidity is applied.